2016
DOI: 10.1177/0194599816666069
|View full text |Cite
|
Sign up to set email alerts
|

Structured Preoperative Phone Counseling by Junior Medical Staff for Improving the Consent Process for Tonsillectomy

Abstract: Preoperative phone counseling by junior medical staff closer to the time of surgery reinforces and clarifies the information previously provided by senior consultants at the time of initial consent for tonsillectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“… 4 , 5 , 8 11 , 13 16 , 19 24 , 27 , 30 , 31 , 33 , 37 43 , 48 50 , 52 57 , 60 62 , 65 , 67 70 , 72 , 73 The level of detail was variable and depended to some extent on the reporting nation; one study broke down education into 5 groups (6–9 years, 9–11 years, high school graduates, some college or vocational school, and college graduates), 70 to sole passage of a graduation exam. 33 In 3 trials, only maternal education was reported 12 , 65 , 67 and one study solely enrolled medical students. 72 …”
Section: What Has Been Tried To Measure and Improve Informed Consent?mentioning
confidence: 99%
See 1 more Smart Citation
“… 4 , 5 , 8 11 , 13 16 , 19 24 , 27 , 30 , 31 , 33 , 37 43 , 48 50 , 52 57 , 60 62 , 65 , 67 70 , 72 , 73 The level of detail was variable and depended to some extent on the reporting nation; one study broke down education into 5 groups (6–9 years, 9–11 years, high school graduates, some college or vocational school, and college graduates), 70 to sole passage of a graduation exam. 33 In 3 trials, only maternal education was reported 12 , 65 , 67 and one study solely enrolled medical students. 72 …”
Section: What Has Been Tried To Measure and Improve Informed Consent?mentioning
confidence: 99%
“… 44 One group used a structured pre-op phone call by junior medical staff to amplify information given at the time of decision to operate. 12 One trial used a 3D model of a patient’s lung with pathology. 56 One trial provided patients with a review of their own images during the consent process.…”
Section: What Has Been Tried To Measure and Improve Informed Consent?mentioning
confidence: 99%